2015
DOI: 10.1186/s40064-015-1088-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bariatric surgery on inspiratory muscle strength

Abstract: BackgroundThe respiratory function is affected by obesity due to an increased deposition of fat on the chest wall. The objective of this study was to investigate the strength of the inspiratory respiratory muscles of obese individuals and the possible influence of bariatric surgery on it by measuring the maximum inspiratory pressure (MIP).MethodsPatients referred to a bariatric centre between the 3rd of October 2011 and the 3rd of May 2012 were screened preoperatively by a multidisciplinary team. Their MIP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…The present results show no difference in MIP and MEP between the pre- and post-surgery conditions and compared to healthy subjects with normal weight. Previous studies showed conflicting results with either unchanged [28], increased [29], or reduced [30] respiratory muscle strength 6 months after bariatric surgery. Type II errors, male/female equilibrium, initial BMI, FM distribution, and loss may account for discrepancies between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The present results show no difference in MIP and MEP between the pre- and post-surgery conditions and compared to healthy subjects with normal weight. Previous studies showed conflicting results with either unchanged [28], increased [29], or reduced [30] respiratory muscle strength 6 months after bariatric surgery. Type II errors, male/female equilibrium, initial BMI, FM distribution, and loss may account for discrepancies between studies.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences between both groups (standard and additional supplementation) were found which suggests that different cholecalciferol supplementation regimen seem to have a little impact on the outcomes. Multiple studies have shown that the SWRT is a reliable indicator for the assessment of cardiopulmonary fitness [19,20,21,22]. The study of Goncalves et al [20] showed that female gender, older age and lower heart rate before the test are the determinants of not reaching maximal effort.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Researchers have reported impaired maximal inspiratory pressure, a clinical marker of inspiratory (diaphragm) muscle strength, in individuals with obesity. [14][15][16][17][18][19] This finding suggests that diaphragm weakness may be a relevant therapeutic target for attenuating dyspnea and improving exercise capacity in this patient population. Preliminary data show improvements in exercise performance and tolerance when individuals with obesity undergo respiratory muscle unloading 20 or training.…”
Section: Introductionmentioning
confidence: 91%